Pengaruh Efikasi Diri Terhadap Kesiapan Pembelajaran Mandiri Mahasiswa Di Jawa Tengah - Robaiyani, Siti; Nurhaliza, Karyati; Aini, Dewi Khurun (Psikologi Prima, 2024)
Independent learning readiness is needed for students due to student-focused learning. However, some students need higher self-learning readiness. This is certainly an obstacle for students when participating in learning activities. The purpose of this study is to empirically examine the effect of self-efficacy on the readiness of students in central java to learn independently. This research is quantitative with an inferential approach. This study used a quantitative approach involving 101 students from central java. The research scale used is independent learning readiness and self-efficacy scales. The data obtained were then analyzed using simple linear regression techniques. The statistical results analyzed using spss showed a significance value of 0.000 <0.05. From these results, self-efficacy has a positive and significant effect on students' readiness for independent learning in central java.